A near-ultraviolet excited broad-spectrum warm white light fluorescent material and preparation and application thereof

CN118026245BActive Publication Date: 2026-10-27DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211368576.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-03
Publication Date
2026-10-27
Estimated Expiration
2042-11-03

AI Technical Summary

Technical Problem

然而,这类材料仍面临着以下问题:激发光范围一般处于较深的紫外波段,导致LED器件所需的开启电压值高;发射光谱峰较窄,难以实现单一材料的宽谱带白光发射

Benefits of technology

[0040]本发明提供的宽光谱Cs3Cu1.5Ag0.5Br5暖白光LED材料,采用简单的溶液一步合成方法,合成简单、快捷、环保、经济。通过本方法合成的宽光谱Cs3Cu1.5Ag0.5Br5材料,白色针状透明晶体,为斜方相,具有独特新奇的准一维晶体结构,不同于常见的全无机Cu基金属卤化物Cs3Cu2Br5、CsCu2Br3与Ag基金属卤化物CsAgBr2。在Cu+、Ag+对晶格的共同调谐作用下,该材料的激发光范围展宽,在240-380nm内均可激发材料荧光。在345nm紫外光激发下,由于自陷激子的辐射跃迁作用,实现了单一组分材料全覆盖可见光区(400-800nm)的连续光谱暖白光发射。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118026245B_ABST
    Figure CN118026245B_ABST
Patent Text Reader

Abstract

The application discloses a near-ultraviolet excited wide-spectrum warm white light fluorescent material and a preparation and application thereof. The white needle-shaped transparent crystal is prepared by one-step synthesis through a solution method, and is a rhombic phase, quasi-one-dimensional metal halide Cs3Cu 1.5 Ag 0.5 Br5. The obtained Cs3Cu 1.5 Ag 0.5 Br5 material has a wide excitation light range (240-380 nm), and under the excitation of 345 nm ultraviolet light, continuous spectrum warm white light emission covering the visible light range (400-800 nm) is realized due to the radiation transition of self-trapped excitons. The preparation method is simple, the obtained metal halide crystal material is environment-friendly, non-toxic, stable and has high efficient wide-spectrum visible light emission performance, and has great development potential in the fields of illumination display, photoelectric detection, X-ray detection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inorganic solid luminescent materials, specifically relating to a near-ultraviolet excited warm white light emitting material, its preparation method, and application scenarios. Background Technology

[0002] All-inorganic lead-free metal halide materials have shown great potential in fields such as solar cells, photodetectors, photocatalysis, and lighting displays due to their lead-free environmental friendliness, excellent photoelectric properties, and good stability, and have been extensively studied in recent years. Currently, researchers have successfully achieved efficient luminescence of low-dimensional metal halides in different emission bands by utilizing the self-trapped exciton radiative transitions common in these materials. However, these materials still face the following challenges: the excitation light range is generally in the deep ultraviolet band, resulting in high turn-on voltages required for LED devices; and the emission spectral peaks are narrow, making it difficult to achieve broadband white light emission from a single material. Therefore, designing and developing novel metal halide materials with low-energy excitation and white light emission is key to realizing their large-scale commercial applications.

[0003] This invention modulates Cu + Ag + The relative content of Cs3Cu was determined, and a novel warm white light material was successfully obtained. 1.5 Ag 0.5 Br5. This material has a novel structure, a simple preparation method, and excellent performance. Figure 2 Cs3Cu is given 1.5 Ag 0.5 Br5 cell structure diagram, where Cu + With Ag + Occupying equivalent structural sites, with Br - It constitutes the tetrahedral unit [CuBr4]. 3- and [AgBr4] 3- (where Br) - Occupying the vertices of the tetrahedron, Cu + or Ag + (Occupying the body center position of the tetrahedron), further, the two tetrahedrons share two Br... - Common edge units are combined to form bitetrahedral elements. Furthermore, bitetrahedral elements share a Br with adjacent bitetrahedral elements. - Forming a one-dimensional chain structure, the chains constructed from double tetrahedrons are connected by Cs. + The atoms are completely separated. Cs3Cu 1.5 Ag 0.5 Br5 belongs to the orthorhombic crystal system with the Cmcm space group structure. Meanwhile, in Cu... + Ag +By utilizing the self-trapped exciton radiation in this material under the co-tuning effect of the crystal lattice, a broadband warm-white light emission covering the visible light region was achieved (Reference 1: Chen, H., Zhu, L., Xue, C. et al. Efficient and bright warm-white electroluminescence from lead-free metalhalides. Nat Commun 12, 1421 (2021). Reference 2: Luo, J., Wang, X., Li, S. et al. Efficient and stable emission of warm-white light from lead-free halide double perovskites. Nature 563, 541–545 (2018)). Summary of the Invention

[0004] Based on existing technologies, this invention proposes a near-ultraviolet excited warm white LED material, its synthesis method, and its application scenarios in lighting displays and X-ray detection.

[0005] The solution adopted by this invention to solve the above-mentioned technical problems is: broadband Cs3Cu 1.5 Ag 0.5 The method for synthesizing Br5 material is characterized by comprising the following steps in sequence:

[0006] 1) Add cesium halide (CsX), cuprous halide (CuX), and silver halide (AgX) (where X = Cl, Br, or I) to a glass container containing a mixed solution of hydrobromic acid (HBr) and hypophosphorous acid (H3PO2). Heat and stir in air to obtain a colorless and transparent solution.

[0007] 2) After the reaction was complete, the mixture was cooled to room temperature to obtain white, needle-like transparent crystals. These were then filtered, and the resulting product was placed in a vacuum drying oven to obtain the final Cs3Cu. 1.5 Ag 0.5 Br5 material.

[0008] According to the above scheme, the molar ratio of cesium halide and cuprous halide in step 1) is 3.5:1-5:1, preferably 3.5:1-4.5:1.

[0009] According to the above scheme, the molar ratio of cuprous halide and silver halide in step 1) is 0.9:1-1.1:1, preferably 0.95:1-1.05:1.

[0010] According to the above scheme, in step 1), the hydrobromic acid is an aqueous solution of hydrobromic acid with a mass percentage concentration of 48-50 wt.%, and the hypophosphoric acid is an aqueous solution of hypophosphoric acid with a mass percentage concentration of 50-52 wt.%, and the volume ratio of the two is 5:1-15:1, preferably 9:1-11:1.

[0011] According to the above scheme, the molar volume ratio of cesium halide to hydrobromic acid in step 1) is 0.6-1 mmol / mL, preferably 0.75-0.85 mmol / mL.

[0012] According to the above scheme, the heating rate in step 1) is 2-5℃ / min, and the reaction temperature reached is 80-120℃, preferably 90-110℃. Furthermore, after reaching the reaction temperature, it needs to be maintained for a period of time, for example, 30-100 minutes, preferably 50-70 minutes.

[0013] According to the above scheme, the cooling rate in step 2) is 3-5℃ / min, and the vacuum drying temperature is 60-80℃, preferably 65-75℃. As an example, the vacuum drying temperature is 70℃. Furthermore, after reaching the vacuum drying temperature, it needs to be maintained for a period of time, for example, 12-24 hours, preferably 20-24 hours.

[0014] This invention provides Cs3Cu obtained by the above preparation method. 1.5 Ag 0.5 Br5 luminescent material.

[0015] Cs3Cu 1.5 Ag 0.5 The structure of Br5 material was characterized and verified by single-crystal X-ray diffraction (SCXRD) and powder X-ray diffraction (PXRD), respectively. The experimental procedure is as follows:

[0016] The crystal structure of the material was tested using a single-crystal X-ray diffractometer (Bruker Smart APEXII03030502, Germany). The material exhibits the following characteristics: Figure 2 The unit cell structure is composed of bitetrahedral structural units sharing Br - The one-dimensional chain and the A-site inorganic cations (Cs) that act as separators between the chains + It is composed of a space group structure with Cmcm symmetry in the orthorhombic crystal system.

[0017] The phase composition of the material was analyzed using a powder X-ray diffractometer (Empyrean-100, Holland), and the material exhibited the following properties: Figure 3 The XRD diffraction pattern.

[0018] Cs3Cu 1.5 Ag 0.5The broad-spectral emission characteristics of Br5 material were characterized by fluorescence spectroscopy, and the experimental procedure is as follows:

[0019] Fluorescence emission spectra were collected under 345 nm UV excitation using a fluorescence spectrometer (Edinburgh FLS1000, England); fluorescence excitation spectra were measured at the 545 nm emission peak, as shown below. Figure 1 The material can be excited in the range of 240-380nm, with the emission peak located at 545nm within the excitation range, and the emission range spanning the entire visible light region (400-800nm).

[0020] Cs3Cu 1.5 Ag 0.5 Br5 material has high luminescence efficiency, with a quantum efficiency of 97.6% under 365nm ultraviolet light excitation.

[0021] Cs3Cu 1.5 Ag 0.5 Br5 materials have stable physicochemical properties.

[0022] The present invention also provides the above-mentioned Cs3Cu 1.5 Ag 0.5 Br5 materials are preferred as the emitting layer of light-emitting diodes and X-ray scintillators in applications such as light-emitting displays, photoelectric detection, and X-ray detection.

[0023] The method for preparing the emitter layer of the metal halide material includes the following steps:

[0024] 1) The synthesized crystal material Cs3Cu mentioned above 1.5 Ag 0.5 Br5 is added to an organic solvent and heated and stirred until completely dissolved.

[0025] 2) Spin-coat the solution from step 1) onto an etched ITO wafer coated with the transport layer material, add an antisolvent, and heat to anneal to form a Cs3Cu layer. 1.5 Ag 0.5 Br5 metal halide thin films.

[0026] The total concentration of the solution in step 1) is 0.15-0.35 mol / L.

[0027] The organic solvent in step 1) is DMSO, DMF, or a mixture of DMSO and DMF.

[0028] The heating temperature in step 1) is 30-50℃, and the stirring speed is 800-1000rpm.

[0029] The antisolvent in step 2) is toluene, chlorobenzene, or ethyl acetate.

[0030] Step 2) The spin coating speed is 2000-3000 rpm and the spin coating time is 30-60 s.

[0031] The heating temperature in step 2) is 50-60℃, and the annealing time is 5-30 minutes.

[0032] The method for preparing the metal halide scintillator thin film includes the following steps:

[0033] 1) Grind the synthesized crystals into powder and mix them evenly with polydimethylsiloxane;

[0034] 2) Add the mixed sample into a polytetrafluoroethylene mold, heat and dry, and cool to room temperature.

[0035] The mass ratio of the crystal powder to polydimethylsiloxane in step 1) is 1:5 to 1:10.

[0036] Step 2) The heating temperature is 100-150℃, the drying time is 30-60min, and the cooling rate is 3-5℃ / min.

[0037] Cs3Cu 1.5 Ag 0.5 Br5 material, as an X-ray scintillator, has a high light yield (~45000ph / MeV) and a low detection limit (45.9nGy / s).

[0038] The present invention also provides a solution containing the above-mentioned Cs3Cu 1.5 Ag 0.5 Br5 material is used in optoelectronic devices such as light-emitting diodes, polarization detectors, and X-ray detectors.

[0039] The beneficial effects of this invention are:

[0040] The broad spectrum Cs3Cu provided by this invention 1.5 Ag 0.5 Br5 warm white LED material was synthesized using a simple one-step solution method, which is simple, fast, environmentally friendly, and economical. Broad-spectrum Cs3Cu was synthesized using this method. 1.5 Ag 0.5 Br5 is a white, needle-like, transparent crystal in the orthorhombic phase, possessing a unique and novel quasi-one-dimensional crystal structure, unlike common inorganic Cu-based metal halides such as Cs3Cu2Br5 and CsCu2Br3, and Ag-based metal halides such as CsAgBr2. In Cu... + Ag +With the combined tuning of the crystal lattice, the excitation range of this material is broadened, and fluorescence can be excited in the range of 240-380 nm. Under 345 nm ultraviolet light excitation, due to the radiative transition of self-trapped excitons, continuous warm white light emission of the single-component material covering the entire visible light region (400-800 nm) is achieved.

[0041] Compared to currently available commercial phosphors, this material enables direct electroluminescent illumination, and its luminescence performance is no longer affected by the aging of blue light chips. Compared to warm white light materials obtained by mixing multi-color phosphors, it reduces complex proportioning and control steps. Compared to element-doped luminescent materials, it eliminates the need for complex feed ratio control and exhibits good stability. Compared to other single-component warm white light materials, this material boasts a high quantum yield, reaching 97.6% under 365nm excitation. In summary, this invention possesses advantages such as novel material structure, high luminescence performance, and simple synthesis method, demonstrating significant development potential and commercial prospects in fields such as lighting displays, photoelectric detection, and X-ray detection. Attached Figure Description

[0042] Figure 1 The broad-spectrum Cs3Cu in Example 1 1.5 Ag 0.5 Fluorescence excitation spectrum (dashed line) and fluorescence emission spectrum (solid line) of Br5 material;

[0043] Figure 2 The broad-spectrum Cs3Cu in Example 1 1.5 Ag 0.5 Unit cell structure obtained by XRD analysis of a single crystal of Br5 material; (where isolated, unbonded ions are Cs) + The tetrahedral structure corresponds to [CuBr4]. 3- Or [AgBr4] 3- ,

[0044] The tetrahedron located at its four vertices is Br - The element located at the center of the tetrahedron is Cu. + or Ag + 。 )

[0045] Figure 3 The broad-spectrum Cs3Cu in Example 1 1.5 Ag 0.5 A comparison of powder XRD patterns and single-crystal simulated XRD patterns of Br5 material;

[0046] Figure 4 The broad-spectrum Cs3Cu in Example 1 1.5 Ag 0.5 A comparison of the powder XRD pattern of Br5 material after ten months of storage with the XRD pattern tested immediately after preparation.

[0047] Figure 5 Broad-spectral Cs3Cu in Example 6 1.5 Ag 0.5 Application of Br5 scintillator thin films in X-ray detection is demonstrated. Detailed Implementation

[0048] The present invention will be further illustrated below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Furthermore, after reading the contents of this invention, those skilled in the art can make any modifications to the present invention, and these equivalent forms also fall within the scope of protection of the present invention.

[0049] Example 1

[0050] Broad spectrum Cs3Cu 1.5 Ag 0.5 The synthesis method of Br5 material is as follows:

[0051] 1) Weigh 0.8512 g (4 mmol) of cesium bromide, 0.1434 g (1 mmol) of cuprous bromide, and 0.1878 g (1 mmol) of silver bromide into a 20 mL glass vial containing 5 mL of hydrobromic acid (48 wt.%) and 0.5 mL of hypophosphoric acid (50 wt.%). Place the vial in an oil bath on an electric heating plate (temperature monitored by a temperature sensor or thermocouple), and heat from room temperature to the reaction temperature of 100 °C at a rate of 4 °C / min. Stir at 100 °C for 1 h. After the reaction is complete, turn off the stirring unit, cool to room temperature at a rate of 1 °C / min, filter rapidly, and place the obtained crystals in a vacuum drying oven at 70 °C for 24 h to obtain Cs3Cu. 1.5 Ag 0.5 Br5 material.

[0052] Figure 1 It is Cs3Cu 1.5 Ag 0.5 The fluorescence excitation spectrum (dashed line) and fluorescence emission spectrum (solid line) of Br5 material. From the excitation spectrum, Cs3Cu... 1.5 Ag 0.5 The excitation cutoff edge of Br5 is approximately 380 nm, therefore we used a 345 nm xenon lamp as the excitation source. Under 345 nm light excitation, a broad peak appeared in the fluorescence emission spectrum in the 400-800 nm range, corresponding to Cs3Cu. 1.5 Ag 0.5 Self-confined exciton luminescence in Br5.

[0053] Figure 2 It is Cs3Cu 1.5 Ag 0.5The unit cell structure of Br5 material obtained by single-crystal XRD analysis is an orthorhombic crystal system, Cmcm space group, quasi-one-dimensional metal halide Cs3Cu. 1.5 Ag 0.5 Br5.

[0054] Cs3Cu 1.5 Ag 0.5 Br5 belongs to the orthorhombic crystal system, space group Cmcm; specifically, Cu + With Ag + Occupying equivalent structural sites, with Br - It constitutes the tetrahedral unit [CuBr4]. 3- and [AgBr4] 3- (where Br) - Occupying the vertices of the tetrahedron, Cu + or Ag + (Occupying the body center position of the tetrahedron), further, the two tetrahedrons share two Br... - Common edge units are combined to form bitetrahedral elements. Furthermore, bitetrahedral elements share a Br with adjacent bitetrahedral elements. - Forming a one-dimensional chain structure, the chains constructed from double tetrahedrons are connected by Cs. + The atoms are completely separated, forming an orthorhombic crystal system with high symmetry (Cmcm).

[0055] Figure 3 It is Cs3Cu 1.5 Ag 0.5 A comparison of the powder XRD pattern and the simulated XRD pattern of the Br5 material is shown. The XRD diffraction peaks of the powder XRD pattern and the simulated XRD pattern of the single crystal correspond well, confirming the correctness of the unit cell structure. Furthermore, the high intensity and narrow peak width of each diffraction peak in the XRD pattern indicate that the prepared Cs3Cu... 1.5 Ag 0.5 Br5 materials have high crystallinity.

[0056] Figure 4 It is Cs3Cu 1.5 Ag 0.5 A comparison of the powder XRD pattern of Br5 material after 10 months of storage with the XRD pattern tested immediately after preparation. The diffraction peaks of the two are well correlated, and no other impurity peaks appear in the former, proving that the material has good stability.

[0057] Example 2

[0058] To test the effects of different reactants on the broad spectrum of Cs3Cu 1.5 Ag 0.5The influence of Br5 material was investigated by replacing the raw materials with CsCl, CsBr, CsI, CuCl, CuBr, CuI, AgCl, AgBr, and AgI (a total of nine groups were synthesized, namely CsCl-CuCl-AgCl, CsCl-CuCl-AgBr, CsCl-CuCl-AgI, CsBr-CuBr-AgCl, CsBr-CuBr-AgBr, CsBr-CuBr-AgI, CsI-CuI-AgCl, CsI-CuI-AgBr, and CsI-CuI-AgI). Other conditions were as follows: HBr volume (5 mL), H3PO2 volume (0.5 mL), molar ratio of CsX to CuX to AgX (4:1:1), molar volume ratio of CsX to HBr (0.8 mmol / mL), solution heating temperature (100 °C), and time (1 h) were all the same as in Example 1. The results showed that the product synthesized entirely using bromide raw materials was homogeneous and free of impurities, containing no CsBr, AgBr, or CuBr impurities. However, materials synthesized using CsCl-CuCl-AgCl, CsCl-CuCl-AgBr, or CsCl-CuCl-AgI raw materials showed peak position shifts and the appearance of CsCl raw material peaks in powder XRD analysis. Materials synthesized using CsBr-CuBr-AgCl raw materials showed the appearance of AgCl raw material peaks in powder XRD analysis. Materials synthesized using CsBr-CuBr-AgI raw materials showed the appearance of AgI raw material peaks in powder XRD analysis. Materials synthesized using CsI-CuI-AgCl, CsI-CuI-AgBr, or CsI-CuI-AgI raw materials showed peak position shifts and the appearance of CsI raw material peaks in powder XRD analysis.

[0059] Example 3

[0060] To examine the molar ratio of cuprous bromide to silver bromide in the broad spectrum of Cs3Cu 1.5 Ag 0.5The influence of Br5 material, except for the molar ratio of cuprous bromide to silver bromide being 0.5:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1, 1.5:1, 2:1, and 3:1, other conditions are as follows: mass of cesium bromide (0.8512 g), mass of cuprous bromide (0.1434 g), volume of HBr (5 mL), volume of H3PO2 (0.5 mL), molar volume ratio of CsBr to HBr (0.8 mmol / mL), solution heating temperature (100 °C), and time (1 h) are all the same as in Example 1. The results showed that when the ratio of cuprous bromide to silver bromide was 0.5:1, 0.8:1, and 0.85:1, the product contained the impurity phase CsAgBr2; when the ratio was 0.9:1, 0.95:1, 1:1, 1.05:1, and 1.1:1, the product was homogeneous and contained no impurity phase; when the ratio was 1.15:1, 1.2:1, 1.5:1, 2:1, and 3:1, the product contained the impurity phase Cs3Cu2Br5. Therefore, in the broad spectrum of Cs3Cu... 1.5 Ag 0.5 In the synthesis of Br5 materials, the optimal molar ratio of cuprous bromide to silver bromide is 0.9:1-1.1:1.

[0061] Example 4

[0062] To examine the molar ratio of cesium bromide to cuprous bromide in the broad-spectrum Cs3Cu 1.5 Ag 0.5 The influence of Br5 material was investigated, except for the molar ratio of cesium bromide to cuprous bromide being 2:1, 3:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 5:1, 5.5:1, and 6:1. Other conditions were the same as in Example 1: cesium bromide mass (0.8512 g), silver bromide mass (0.1878 g), HBr volume (5 mL), H3PO2 volume (0.5 mL), molar volume ratio of CsBr to HBr (0.8 mmol / mL), solution heating temperature (100 °C), and time (1 h). The results showed that when the cesium bromide to cuprous bromide ratio was 2:1, powder XRD analysis revealed the presence of CuBr impurities in the product; while when the cesium bromide to cuprous bromide ratio was 6:1, powder XRD analysis revealed the presence of CsBr impurities in the product. Meanwhile, when the ratio of cesium bromide to cuprous bromide is 3:1, the target product is homogeneous, but the yield is significantly low, approximately 40%. When the ratio is 5:1, the synthesized product is free of impurities, but this results in a waste of the starting material CsBr. When the ratios of cesium bromide to cuprous bromide are 3.5:1, 3.8:1, 4:1, 4.2:1, and 4.5:1, the product is homogeneous and free of impurity phases. Therefore, in the broad-spectrum Cs3Cu...1.5 Ag 0.5 In the synthesis of Br5 materials, the optimal molar ratio of cuprous bromide to silver bromide is 3.5:1-4.5:1.

[0063] Example 5

[0064] To examine the effect of vacuum drying oven temperature during the post-processing stage on the broad spectrum of Cs3Cu 1.5 Ag 0.5 The influence of Br5 material was investigated. Except for the vacuum drying oven temperatures of 50, 60, 70, 80, 90, 100, and 120°C, other conditions were the same as in Example 1: cesium bromide mass (0.8512 g), HBr volume (5 mL), H3PO2 volume (0.5 mL), molar ratio of CsBr to CuBr to AgBr (4:1:1), molar volume ratio of CsBr to HBr (0.8 mmol / mL), solution heating temperature (100°C), and time (1 h). Results showed that at a drying temperature of 50°C, due to the low temperature, after 24 hours of vacuum drying, a small amount of residual solvent remained, causing fogging on the bottle. At drying temperatures of 90°C, 100°C, and 120°C, due to the instability of monovalent copper, the product turned purple shortly after removal, and some Cu... + Oxidation occurred; when drying at 60℃, 70℃, and 80℃, no solvent residue remained, and the product showed no color change after removal. Powder XRD analysis revealed that the product was homogeneous and free of impurities. Therefore, in a broad-spectrum Cs3Cu... 1.5 Ag 0.5 During the synthesis of Br5 materials, the optimal temperature range for the vacuum drying oven is 60-80℃.

[0065] Example 6

[0066] Broad spectrum Cs3Cu 1.5 Ag 0.5 The preparation method of Br5 material scintillator thin film is as follows:

[0067] 0.5g of Cs3Cu 1.5 Ag 0.5 Br5 crystals were ground into powder and mixed evenly with 5g of polydimethylsiloxane. The mixed sample was added into a polytetrafluoroethylene mold, heated to 150℃ and dried for 30min, and then cooled to room temperature at a rate of 4℃ / min. A flat scintillator film sample with a thickness of about 1mm was obtained, which showed yellowish-white luminescence under X-ray irradiation.

[0068] Figure 5 It is Cs3Cu 1.5 Ag 0.5The application of Br5 scintillator thin films in X-ray detection was demonstrated. Specifically, an X-ray source was used to illuminate a lighter, and the signal was transmitted through the thin film sample to a camera for imaging. The results showed that the fabricated scintillator thin film could clearly reveal the spring mechanism inside the lighter. This demonstrates the potential of this material as a scintillator unit in X-ray detectors.

Claims

1. A method for preparing a near-ultraviolet-excited broadband warm white fluorescent material, characterized in that, The chemical formula of the material is Cs3Cu 1.5 Ag 0.5 Br5; Cs3Cu 1.5 Ag 0.5 Br5 belongs to the orthorhombic crystal system, space group Cmcm; Cu + With Ag + Occupying equivalent structural sites, with Br - It constitutes the tetrahedral unit [CuBr4]. 3- and [AgBr4] 3- , of which Br - Occupying the vertices of the tetrahedron, Cu + or Ag + Occupying the body center position of the tetrahedron, the two tetrahedrons share two Br. - Common edge elements are combined to form bitetrahedral elements, which share a common edge with adjacent bitetrahedral elements. - Forming a one-dimensional chain structure, the chains constructed from double tetrahedrons are connected by Cs. + The atoms are completely separated; The specific steps are as follows: 1) Add cesium bromide, cuprous bromide, and silver bromide to a mixed solution of hydrobromic acid and hypophosphoric acid; heat and stir in air to obtain a colorless and transparent solution; 2) After the reaction was completed, the mixture was cooled to room temperature to obtain white needle-like transparent crystals; then solid-liquid separation was performed, and the obtained solid product was dried to obtain the final Cs3Cu. 1.5 Ag 0.5 Br5 material.

2. The preparation method according to claim 1, characterized in that, In 1), the molar ratio of cesium bromide to cuprous bromide is 3.5:1-5:1; The molar ratio of cuprous bromide to silver bromide is 0.9:1 to 1.1:1; Hydrobromic acid is an aqueous solution with a mass percentage concentration of 48-50 wt.%, and hypophosphoric acid is an aqueous solution with a mass percentage concentration of 50-52 wt.%, with a volume ratio of 5:1-15:

1. The molar volume ratio of cesium bromide to hydrobromic acid is 0.6–1 mmol / mL; The reaction temperature is 80-120 ℃. The temperature is increased from room temperature to the reaction temperature at a rate of 3-5 ℃ / min, and then maintained for 30-100 minutes after reaching the reaction temperature.

3. The preparation method according to claim 2, characterized in that, The molar ratio of cesium bromide to cuprous bromide is 3.5:1 to 4.5:

1.

4. The preparation method according to claim 1, characterized in that, In step 2), the cooling rate to room temperature is controlled at 2-5℃ / min, the vacuum drying temperature is 60-80℃, and the vacuum drying temperature is maintained for 12-24 hours after reaching the vacuum drying temperature.

5. A method for preparing Cs3Cu according to any one of claims 1-4 1.5 Ag 0.5 Br5 material.

6. A Cs3Cu according to claim 5 1.5 Ag 0.5 Applications of Br5 materials in lighting displays, photoelectric detection, or X-ray detection.

7. The application according to claim 6, characterized in that, The Cs3Cu 1.5 Ag 0.5 Br5 material can be used as the emitting layer of a light-emitting diode, or directly as a phosphor, or as a linearly polarized light recognition unit in a polarization photodetector, or as a scintillator unit in X-ray detection.

8. A substance containing the Cs3Cu of claim 5 1.5 Ag 0.5 Optoelectronic devices made of Br5 material.

9. The optoelectronic device according to claim 8, characterized in that, The optoelectronic device is a light-emitting diode, a polarization detector, or an X-ray detector.

Citation Information

Patent Citations

  • Copper-doped zero-dimensional all-inorganic zinc halide compound material as well as synthesis and application thereof

    CN113831914A

  • Novel perovskite-like structure scintillator for neutron detection as well as preparation method and application of novel perovskite-like structure scintillator

    CN114411252A